2005
DOI: 10.7748/paed.17.10.31.s23
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre research: lessons from the field

Abstract: Multicentre research can be used to explore and generate significant data in aspects of care that affect small numbers of children. This article describes the problems and benefits encountered by a group of nurses from 11 hospitals undertaking a multicentre study of pressure ulcers in children and young people in England and Wales. Multicentre research can generate a large amount of useful data contributing to high quality evidence-based care and can provide nurses with a valuable learning and networking exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In the rehabilitation care setting, chronically ill as well as physically handicapped children are treated. Immobility and reduced sensation has been previously defined as a major risk factor in the study of Willock et al. (2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the rehabilitation care setting, chronically ill as well as physically handicapped children are treated. Immobility and reduced sensation has been previously defined as a major risk factor in the study of Willock et al. (2005).…”
Section: Discussionmentioning
confidence: 99%
“…Further potential risk factors mentioned are immobility and decreased skin sensitivity (Suddaby et al. 2005, Willock 2005, Willock et al. 2005).…”
Section: Introductionmentioning
confidence: 99%
“…3 Several studies have found that PU is also a common problem in pediatrics population. 4 The prevalence of childhood hospital ulcers varies from 3% to 35%. 5 In pediatrics population, the risk factors for the formation of known ulcers include immobility and decreased skin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Challenges of multi-centred studies have been documented to include high financial cost, difficulty maintaining scientific integrity and logistical problems (e.g. the requirement of multiple ethics and research governance submissions).…”
mentioning
confidence: 99%
“…Multi-centred trials are becoming increasingly common in health research as they allow researchers to gather large sample sizes that enable increased statistical power, more timely recruitment, clinically meaningful research, and enable generalisability of results. [1][2][3][4][5] Challenges of multi-centred studies have been documented to include high financial cost, difficulty maintaining scientific integrity and logistical problems (e.g. the requirement of multiple ethics and research governance submissions).…”
mentioning
confidence: 99%